Genetic Variation in Calcium Channel Gene in Idiopathic Generalized Epilepsies - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2008)
Researchers at Women's And Children's Hospital, North Adelaide, and other centers in Australia and Canada screened 240 individuals from 167 families with idiopathic generalized epilepsy and generalized epilepsy with febrile seizures plus (GEFS + ) and 95 controls for variants in the CACNA1H gene.